Extracellular vesicle-derived MicroRNAs as potential therapies for spinal cord and peripheral nerve injuries - Young-Ju Lim; Min-Soo Seo; Wook-Tae Park; Sangbum Park; Gun Woo Lee (RNA Biology)
Complete nerve regeneration is limited in current therapeutic approaches for spinal cord injuries (SCIs) and peripheral nerve injuries (PNIs). Extracellular vesicles (EVs) and microRNAs (miRNAs) play a pivotal role in intercellular communication by transporting various biomolecules, including miRNAs, to the recipient cells. Thus, they are promising targets for novel neural regeneration drugs. This comprehensive study examined the roles of EV-derived miRNAs in facilitating neural rejuvenation after SCI and PNI. It also explored the mechanisms by which they augment neuroprotection and promote cell viability. It also discusses their translational potential for treating nerve injury and evaluates their potential impact on advancements in nerve resurrection and prospective research in regenerative medicine. The findings may provide effective treatments and improve outcomes, as well as contribute to addressing the direction for the next studies, for the pathologies of SCI and PNI.